PERANCANGAN WIRELESS SENSOR NETWORK MENGGUNAKAN TEKNOLOGI MULTISENSOR SEBAGAI SISTEM MONITORING KUALITAS UDARA - Ade Silvia; R.A Halimatussa’diyah2; Rahmad Rizky Aldi; Nyayu Latifah (Jurnal Qua Teknika, 2020)
Along with the current development, air quality is very vulnerable to being polluted. Factors that affect air quality are an increase in infrastructure development, factories, motor vehicle fumes and any other human activity. Based on these factors, an air quality monitoring system that is integrated into a Wireless Sensor Network (WSN) system is needed. In this study, a Wireless Sensor Network will be designed using Multisensor Network technology that works in real time to measure pollutant gas levels using the TGS 2442 sensor as a measure of carbon monoxide (CO) , MG811 sensor as a measure of carbon dioxide (CO2) , TGS 2611 sensor as a measure of HydroCarbon (HC), the DHT-11 sensor as a temperature and humidity meter and the SHARPGP2Y1010 sensor as a measure of particulate levels in the air (PM10). The data from this sensor reading is sent to the server using a Raspberry pi microprocessor. Furthermore, the data will be processed until it becomes information that can be used by users or the general public.